(3eLGdS GdCHQGQ heSGdc GdCNjGQs - (3GdbHQSj, GdQhej, CMeO Hf YHO GdbGgQ, J(B1043(3g`s
(3ChdgG (B:s
(3GdeLdS GdChd aj HjGf PcQ Gddg JYGdi bGd QShd Gddg Udi Gddg Ydjg hSde eKd GdPj jPcQ QHg hGdPj dG jPcQ QHg eKd GdMj hGdejJ gPG GdMOjK ef UMGM GdeUGHjM QhGg CHh ehSi GdCTYQjs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3eG Ydjg ef GdegQ hfMhg dCf GdQVGA TQW aj dRhe GdeGd hSbhWg hdG cQGg jbOe GdQVG Ydi eG Hjf aj ehVYgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 154s
(3eYLe GdeDdajf(B: 1 / 174s
(3cTa GdXfhf(B: 2 / 1590s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs